Vital Analysis: Annotating sensed physiological signals with the stress levels of first responders in action - Gomes, P (2012)
First responders such as firefighters are exposed to extreme stress and fatigue situations during their work routines. It is thus desirable to monitor their health using wearable sensing but this is a complex and still unsolved research challenge that requires large amounts of properly annotated physiological signals data. In this paper we show that the information gathered by our Vital Analysis Framework can support the annotation of these vital signals with the stress levels perceived by the target user, confirmed by the analysis of more than 4600 hours of data collected from real firefighters in action, including 717 answers to event questionnaires from a total of 454 different events.